Studi Komparasi Perhitungan Return Deposito Syari’ah di BSM dengan Deposito Konvensional di Bank Mandiri - Syaparuddin Syaparuddin (Faculty of Sharia and Law - Sunan Kalijaga State Islamic University, 2015)
This study aims to find out: (1) the calculating methode of time-deposit return in BSM and Bank Mandiri, and (2) if BSM or Bank Mandiri gives a better time-deposit return to itself and its customers. The result of this study showed that the return of BSM is higher than that of Bank Mandiri. However, the profit which BSM gets is uncertain because the return which will be given to its customers depends on the income of BSM which gets. It means that the return of mudhârabah time-deposit which BSM gives to its customers is uncertain, whereas the return of time-deposit which Bank Mandiri gives to its customers is certain and almost no any risk will appear. But if the risk of that is lower, its return will be lower too. If it is so, the public will no get a high profit if they avoid any risk, because the higher return they will expect, the higher risk they will face. Risk and return always have a positive relationship. If the public understand this problem, they will choose the Islamic Bank (BSM) to deposit their money. Abstrak: Penelitian ini bertujuan (1) un